DISCUSSIONS OVER A CASE OF JUVENILE IDIOPATHIC ARTHRITIS - PULMONARY FIBROSIS - Alice Raica; Ioan Popa; Liviu Pop; Timofte Adelina Minerva; Simona Danci (Amaltea Medical Publishing House, 2009)
The authors present the case of an 18-year-old boy with juvenile idiopathic arthritis associated with pulmonary fibrosis. The diagnosis was established on American College of Rheumatology criteria. There were presented the differential diagnosis, the treatment, the evolution, the prognosis and the conclusions.